Model Pendidikan Spiritual Anak Islami dan Pengaruhnya terhadap Peningkatan Perilaku Komunikasi dengan Non-Coreligionist - Amirudin, Faisol; Yasa, Ahmad; Fathurahman, Asep Ahmad (ALSYS, 2023)
This document examines how spiritual education affects a child's communication skills through presenting an Islamic model based on Quran and prophetic tradition. First, this paper discusses spirituality from a theoretical perspective. Then, it provides a brief history of how children worldwide have been taught spirituality. Next, this presentation presents the Islamic model of spirituality that includes its moral foundations and aspects. Finally, this paper provides a conceptual analysis of spiritual education with a short history of its focus. The current paper discusses the key aspects of Islamic Model for Children’s Spiritual Education that help the children practice their communication skills with people from different religions. These findings were gathered through a descriptive-analytic process.